Soil and leaf nutrient status on growth of Macaranga gigantea in secondary forest after shifting cultivation in East Kalimantan, Indonesia - DWI SUSANTO; DADDY RUCHIYAT; MAMAN SUTISNA; RUDIANTO AMIRTA (Society for Indonesian Biodiversity, 2016)
Susanto D, Ruchiyat D, Sutisna M, Amirta R. 2016. Soil and leaf nutrient status on growth of Macaranga gigantea in secondary forest after shifting cultivation in East Kalimantan, Indonesia. Biodiversitas 17: 409-416. Macaranga gigantea is an important pioneer plant species in the tropical secondary forest of Kalimantan and as far the attractive wood species was not commercially cultivated. This study aims to determine the soil and nutrient status on growth of M. gigantea in the secondary forest particularly after shifting cultivation activity. For this purposes, the observation plots with 50m x 50m sizes were made and measured to collect the data of diameter, height, soil conditions and leaf nutrient concentrations -1 and 2.96 year -1 and it was gradually decreased until the 10 years old of plant. The negative correlations was observed from the soil nutrient K and growth of diameter and high of M. gigantea and this nutrient factor should be considered well when this species will be cultivated for the commercial purposes in the future.